Traffic Infrastructure and Economics Development in the Republic of Croatia - Šimulčik, Damir; Ban, Ivo (Promet - Traffic&Transportation, 2012)
Traffic infrastructure makes an integral pwt of the trafficand economic system in each country. The traffic policy makershave a task, that their policy must be based on scientific developmentsand synchronised activity of all economic systemsegments.